Modern library and reading in multimedia environment - V. Ya. Askarova (Библиосфера, 2020)
The article identifies the library's ability to stimulate reader activity in the context of the multimedia culture development. It also considers main changes in the library activities as an organizer of reading in multimedia culture including the increase of emphasis on readers, their subjectivity, interaction dialogue forms development, multimedia projects implementation, online services and digital resources introduction, education of readers on literate media behavior and text activity in the Internet. The author states that in the context of multimedia, library can become an active participant in overcoming information chaos, streamlining information flows, enhancing reading and also contribute to the development of inter-reader communication. The article concludes that it is necessary to prepare library specialists, tutors, ready to organize communication about books and reading in a real and virtual environment, network navigation, analysis of Internet resources, recognition of misinformation, and teaching readers various techniques of textual activity.